PENGGUNAAN METODE “PERANG MENTAL MATEMATIKA” DENGAN MENGGUNAKAN MEDIA KARTU PECAHAN PADA MATERI PENJUMLAHAN BILANGAN PECAHAN - Indah Suciati (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2020)
Fractions are a subset of a set of real numbers. Although the form is simple and often used in everyday, but the material about fractions especially in the addition of fraction numbers is still complicated for students. To overcome this problem, a solution is given in the form of the method of " Mathematical Mental Wars ". Mathematical Mental Wars is the presentation of a fast, interesting, and interactive way for students to practice problems with variables, equations, and answers. The steps of the method of " Mental Wars Mathematics ", namely: (1) reviewing game cards, (2) reviewing traditional war card games and explaining the rules and procedures, (3) grouping students in pairs, (4) providing each pair with The set of fractional cards to be shared equally, (5) reminds students not to open cards until the game starts and (6) starts the game.